Nudegusių ligonių ir jų žaizdų patogenų analizė - Rokas Bagdonas; Algimantas Tamelis; Rytis Rimdeika; Mindaugas Kiudelis (Lietuvos Chirurgija, 2004)
Rokas Bagdonas, Algimantas Tamelis, Rytis Rimdeika, Mindaugas Kiudelis